The Influence Of Career Development And Work Environment On Employee Performance Through Work Motivation At The Deputy Work Unit For Legal And Cooperation Affairs Of The BNN - Maya Rosyalina; Iwan Kurniawan Subagja (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study aims to: 1) examine and analyze the influence of career development and work environment on employee performance, 2) examine and analyze the influence of career development and work environment on work motivation, 3) examine and analyze the influence of work motivation on employee performance, 4) examine and analyze the influence of career development on employee performance through work motivation, and 5) examine and analyze the influence of the work environment on employee performance through work motivation. The research was conducted at the Legal Affairs and Cooperation Unit of BNN, with a sample size of 60 respondents. The sample collection technique used a questionnaire. The data analysis method employed descriptive and path analysis. The research results show that: 1) career development and work environment influence employee performance, 2) career development and work environment influence work motivation, 3) work motivation influences employee performance, 4) career development does not influence employee performance through work motivation, and 5) the work environment does not influence employee performance through work motivation. The work motivation variable cannot mediate the effect of career development and work environment on improving employee performance.